Men's Discourses of Depression - Galasinski, D. author. aut Link
VIII, 209 p.
Keywords: An original and timely study of men's experiences of depression in which the author tackles the discursively constructed relationship between the self and depression showing its linguistic and social complexity and analyses the relationship between depression and masculinity.